Global Quality of Life in HIV/AIDS Patients: A Systematic Review and Meta-Analysis - Fatemeh Pashazadeh Kan; Zahra Hoseinipalangi; Samira Raoofi; Sima Rafiei; Hossein Hosseinifard; Maryam Masoumi; Hooman Koohestan; Afsaneh Dehnad; Sepideh Aghalou; Faranak Rokhtabnak; Azadeh Laali; Saba Ahmadi; et al. (Shiraz University of Medical Sciences, 2023)
Background: Acquired immunodeficiency syndrome (AIDS) caused by the human immunodeficiency virus (HIV) is known as one of the most chronic conditions, having significant effects on physical and mental health status in infected individuals, and thus reducing their quality of life (QoL).Methods: I n t his s ystematic r eview, t he d ata w ere i nitially collected from the databases of Scopus, PubMed, Embase, Web of Science, and Google Scholar from January 2000 to September 2020 based on the inclusion and exclusion criteria of the study. The data were then analyzed by using the R software.Results: A total number of 25 research articles addressing the QoL in 5,952 HIV/AIDS patients were evaluated using three valid questionnaires, including the Medical Outcomes Study HIV Health Survey (MOS-HIV), the 36-Item Short Form Health Survey (SF-36), and the World Health Organization Quality of Life in HIV-Infected Persons (WHOQoL-HIV). Based on the MOS-HIV, the SF-36, and the WHOQoL-HIV questionnaires, the QoL mean scores in HIV/AIDS patients were 51.80 (49.4- 54.57), 54.81 (52.68-56.93), and 13.62 (11.97-15.26), respectively. In addition, the physical items gained a higher mean score than the mental ones in all the questionnaires. The QoL showed higher mean scores in the SF-36 and the WHOQoL-HIV questionnaires in Africa, except for the MOS-HIV questionnaire, which had the highest mean score in North America.Conclusion: Overall, the QoL in HIV/AIDS patients in this study was acceptable, even though further changes and studies are still required to support the findings.